2021
DOI: 10.1158/2767-9764.crc-21-0064
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1/ATF1-Mediated Transactivation is Involved in Resistance to PARP Inhibitors and Cisplatin

Abstract: Homologous recombination (HR)-deficient cells are sensitive to PARP inhibitors through a synthetic lethal effect. We previously developed an HR activity assay named Assay of Site-Specific HR Activity (ASHRA). Here, we evaluated the HR activity of 30 missense variants of BRCA1 by ASHRA and found that several BRCA1 variants showed intermediate HR activity, which was not clearly discerned by our previous analyses using a conventional method. HR activity measured by ASHRA was significantly correlated with sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…Finally, we identified three patient-derived variants, which reduced the interaction of BRCA1 with Aurora A (Figure 7E). The N132K variant, which moderately decreases homologous recombination activity, 53 The present data suggest that, in response to nuclear DNA damage, BRCA1 is phosphorylated by ATM in the nucleus, moves to the cytoplasm, localizes to the centrosome, and promotes the centrosomal localization of Aurora A, which phosphorylates PLK1. Activated PLK1 causes premature centriole disengagement and centriole overduplication, leading to DDICA (Figure 8).…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Finally, we identified three patient-derived variants, which reduced the interaction of BRCA1 with Aurora A (Figure 7E). The N132K variant, which moderately decreases homologous recombination activity, 53 The present data suggest that, in response to nuclear DNA damage, BRCA1 is phosphorylated by ATM in the nucleus, moves to the cytoplasm, localizes to the centrosome, and promotes the centrosomal localization of Aurora A, which phosphorylates PLK1. Activated PLK1 causes premature centriole disengagement and centriole overduplication, leading to DDICA (Figure 8).…”
Section: Discussionsupporting
confidence: 49%
“…Finally, we identified three patient‐derived variants, which reduced the interaction of BRCA1 with Aurora A (Figure 7E ). The N132K variant, which moderately decreases homologous recombination activity, 53 reduced the CDDP‐induced centrosomal localization of BRCA1 and Aurora A, whereas V191I reduced that of only Aurora A (Figure 7F,G ). The Y105C variant, which induced a mild reduction of the BRCA1–Aurora A association compared with N132K and V191I, did not affect the CDDP‐induced centrosomal localization of BRCA1 and Aurora A.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of missense variants on BRCA1 have been tested in a number of studies by analyzing one variant at a time in the HDR assay-the singleton assay [8,13,[28][29][30][31][32]. For the current study, we have analyzed 18 different variants in the singleton assay (Fig 6A) in addition to variants in the BRCA1 amino-terminus that have been previously published [8,12,17,33].…”
Section: Plos Geneticsmentioning
confidence: 99%
“…In the case of BRCA1, previous studies have suggested that its function in homology directed repair of DNA double-strand breaks is key to its tumor suppressor activity [3,[8][9][10][11]. Cells with a loss of BRCA1 function in homology directed repair assays exhibit heightened sensitivity to DNA-damaging agents and PARP inhibitors [12][13][14][15]. The use of multiplexed approaches to analyze many hundreds to thousands of variants at once [3,8,9,12,16] enable the analysis of many variants that are rare in the population.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the inhibition of the VEGF pathway on HR activity was evaluated using ASHRA to elucidate the mechanism of sensitization to olaparib by the inhibition of the VEGF pathway. ASHRA can quantify cellular HR activity, and the measured activity in ASHRA correlates linearly with sensitivity to PARP inhibitors 23 . The treatment with the addition of bevacizumab or cediranib signi cantly suppressed the HR activity in OVISE cells (Fig.…”
Section: Inhibition Of the Vegf Signaling Pathway Suppressed Hr Activ...mentioning
confidence: 99%